Acrylic Diblock Copolymers/Clay Nanocomposites Via In Situ Nitroxide Mediated Polymerization. Issue 13 (1st June 2015) - Cherifi, Nabila; BenAboura, Ahmed; Save, Maud; Billon, Laurent
<x xml:space="preserve">Abstract</x> The first nitroxide‐mediated polymerization of butyl acrylate/methyl methacrylate and/or styrene diblock copolymers‐based nanoclay composites is reported. Polybutyl acrylate (PBA) macroinitiators synthesized in the presence of raw and modified clays are used for chain extension. All materials are characterized by proton nuclear magnetic resonance, size exclusion chromatography, X‐ray diffraction, thermogravimetric analysis, and differential scanning calorimetry techniques. The obtained proton nuclear magnetic resonance and size exclusion chromatography results show that all syntheses are carried out in controlled manner. X‐ray diffraction analysis of hybrid materials reveals the formation of different structures varying between exfoliated and disordered ones. These structures depend on nanoclay distribution in different (co)polymer matrix and probable polymer/nanoclay interactions. All PBA composites and hybrid diblock materials register the enhanced thermal stability and show two glass transition temperature Tg values corresponding to the two diblock acrylic macromolecular features.